Cutaneous Rhinosporidiosis - Bandyopadhyay Debabrata (Wolters Kluwer Medknow Publications, 1997)
A case of cutaneous rhinosporidiosis mimicking verucca vulgaris involving an eyelid in a young male patient is described.